Text Line Extraction of Handwritten Kannada Documents Based on Bounding Box Technique - Chethana, HT; Mamatha, HR (International Journal of Computer Sciences and Engineering, 2015)
Optical Character Recognition is the process of transforming printed or handwritten text in to a form in which computer can understand and manipulate. An important task of any Optical Character Recognition(OCR)system is segmentation. Characters, words and lines are separated from image text documents by segmentation. Depending on the segmentation algorithm which is being used can affect the accuracy of OCR system. Segmentation of handwritten Kannada script poses challenges due to writing styles, skewed lines, overlapping lines, inter and intra word gaps. In this paper we have proposed method for segmentation of handwritten Kannada documents based on bounding box and morphological operations, an average segmentation rate of 92% for lines is obtained.